New insights into the use of currently available non-steroidal anti-inflammatory drugs - Brune, Kay; Patrignani, Paola (Journal of Pain Research, 2015)
Non-steroidal anti-inflammatory drugs (NSAIDs), which act via inhibition of the cyclooxygenase (COX) isozymes, were discovered more than 100 years ago. They remain a key component of the pharmacological management of acute and chronic pain. The COX-1 and COX-2 isozymes have different biological functions; analgesic activity is primarily (although not exclusively) associated with inhibition of COX-2, while different side effects result from the inhibition of COX-1 and COX-2. All available NSAIDs, including acetaminophen and aspirin, are associated with potential side effects, particularly gastrointestinal and cardiovascular effects, related to their relative selectivity for COX-1 and COX-2. Since all NSAIDs exert their therapeutic activity through inhibition of the COX isozymes, strategies are needed to reduce the risks associated with NSAIDs while achieving sufficient pain relief. A better understanding of the inhibitory activity and COX-1/COX-2 selectivity of an NSAID at therapeutic doses, based on pharmacokinetic and pharmacodynamic properties (eg, inhibitory dose, absorption, plasma versus tissue distribution, and elimination), and the impact on drug tolerability and safety can guide the selection of appropriate NSAIDs for pain management. For example, many NSAIDs with moderate to high selectivity for COX-2 versus COX-1 can be administered at doses that maximize efficacy ( 80% inhibition of COX-2) while minimizing COX-1 inhibition and associated side effects, such as gastrointestinal toxicity. Acidic NSAIDs with favorable tissue distribution and short plasma half-lives can additionally be dosed to provide near-constant analgesia while minimizing plasma concentrations to permit recovery of COX-mediated prostaglandin production in the vascular wall and other organs. Each patient's clinical background, including gastrointestinal and cardiovascular risk factors, should be taken into account when selecting appropriate NSAIDs. New methods are emerging to assist clinicians in the selection of appropriate NSAIDs and their doses/schedules, such as biomarkers that may predict the response to NSAID treatment in individual patients.
EVALuna2:8746